Enhanced sucrose fermentation by introduction of heterologous sucrose transporter and invertase into Clostridium beijerinckii for acetone–butanol–ethanol production. Issue 9 (22nd September 2021) - Lin, Lihua; Zhang, Zhikai; Tang, Hongchi; Guo, Yuan; Zhou, Bingqing; Liu, Yi; Huang, Ribo; Du, Liqin; Pang, Hao
Abstract : A heterologous pathway for sucrose transport and metabolism was introduced into Clostridium beijerinckii to improve sucrose use for n -butanol production. The combined expression of StSUT1, encoding a sucrose transporter from potato ( Solanum tuberosum ), and SUC2, encoding a sucrose invertase from Saccharomyces cerevisiae, remarkably enhanced n -butanol production. With sucrose, sugarcane molasses and sugarcane juice as substrates, the C. beijerinckii strain harbouring StSUT1 and SUC2 increased acetone–butanol–ethanol production by 38.7%, 22.3% and 52.8%, respectively, compared with the wild-type strain. This is the first report to demonstrate enhanced sucrose fermentation due to the heterologous expression of a sucrose transporter and invertase in Clostridium . The metabolic engineering strategy used in this study can be widely applied in other microorganisms to enhance the production of high-value compounds from sucrose-based biomass.